Intermediate addition multifocals provide safe stair ambulation with adequate 'short‐term' reading. (25th August 2015) - Elliott, David B.; Hotchkiss, John; Scally, Andrew J.; Foster, Richard; Buckley, John G.
Abstract: Purpose: A recent randomised controlled trial indicated that providing long‐term multifocal wearers with a pair of distance single‐vision spectacles for use outside the home reduced falls risk in active older people. However, it also found that participants disliked continually switching between using two pairs of glasses and adherence to the intervention was poor. In this study we determined whether intermediate addition multifocals (which could be worn most of the time inside and outside the home and thus avoid continual switching) could provide similar gait safety on stairs to distance single vision spectacles whilst also providing adequate 'short‐term' reading and near vision. Methods: Fourteen healthy long‐term multifocal wearers completed stair ascent and descent trials over a 3‐step staircase wearing intermediate and full addition bifocals and progression‐addition lenses (PALs) and single‐vision distance spectacles. Gait safety/caution was assessed using foot clearance measurements (toe on ascent, heel on descent) over the step edges and ascent and descent duration. Binocular near visual acuity, critical print size and reading speed were measured using Bailey‐Lovie near charts and MNRead charts at 40 cm. Results: Gait safety/caution measures were worse with full addition bifocals and PALs compared to intermediate bifocals and PALs. The intermediate PALs provided similar gait ascent/descent measures to those with distance single‐vision spectacles. The intermediate addition PALs also provided good reading ability: Near word acuity and MNRead critical print size were better with the intermediate addition PALs than with the single‐vision lenses ( p < 0.0001), with a mean near visual acuity of 0.24 ± 0.13 logMAR ( N5.5) which is satisfactory for most near vision tasks when performed for a short period of time. Conclusions: The better ability to 'spot read' with the intermediate addition PALs compared to single‐vision spectacles suggests that elderly individuals might better comply with the use of intermediate addition PALs outside the home. A lack of difference in gait parameters for the intermediate addition PALs compared to distance single‐vision spectacles suggests they could be usefully used to help prevent falls in older well‐adapted full addition PAL wearers. A randomised controlled trial to investigate the usefulness of intermediate multifocals in preventing falls seems warranted.